TREATMENT OF TRIPLE-NEGATIVE BREAST CANCER - A. D. Zikiryakhodzhaev; M. A. Frolova; E. A. Rasskazova; E. V. Glazkova (ABV-press, 2017)
The rate of triple-negative breast cancer is 10-24  %, and in recent years it's one of the most studied subtypes of breast cancer due to its clinical aggressiveness and a small number of molecular targets.The study objective is to evaluate effectiveness of different NAPCT regimens including their dependence on the presence of mutations in the ВRСА 1, 2, СHEK2 genes.Materials and methods. The study included 40 female patients with triple-negative breast cancer. The patients were monitored from 2012 to 2016; surgical treatment was performed at the P.A. Hertzen Moscow Oncology Research Institute - branch of the National Medical Research Radiological Center, Ministry of Health of Russia. Median patient age was 45.9 (31-69)  years. All patients received neoadjuvant polychemotherapy (NAPCT) per different regimens. Then the patients underwent surgery of different volume (from radical mastectomies to resections), and in 25 % of cases reconstructive breast surgery was performed. In 5 patients with BRCA1, - 2 mutations, prophylactic subcutaneous mastectomy with immediate reconstruction with an implant was performed; 2 patients refused prophylactic mastectomy; in 1 patient with СНЕК2 mutation, metachronous multiple primary breast cancer was diagnosed, previously she didn»t undergo prophylactic mastectomy, and 6 years later cancer in the second breast was diagnosed.Results. The study included 11 patients under 40 (27.5 %), 4 (50 %) of them in the group with mutations in ВRCA1, -2, CHEK2.The study demonstrated high effectiveness of NAPCT regimens per the АС + Т scheme and weekly injections of doxorubicin 25 mg/m2, cisplatin 30 mg/m2, and paclitaxel 100 mg/m2. Grade IV treatment pathomorphosis for NAPCT per АС + Т scheme was achieved in 50.0 ± 7.9 % cases, for intensified regimen - in 62.5 ± 12.5 % cases.Median follow-up duration for this patient group was 22.1 months, and during this time disease progression was observed in 3 patients: in the 1st patient continued growth on the thoracic wall and brain metastases were diagnosed, in the 2nd patient - lung and supraclavicular lymph nodes metastases, in the 3rd patient - metastases in the cerebellum. In all of these patients, grade IV treatment pathomorphosis wasn»t achieved. Conclusions. The study demonstrated high effectiveness of NAPCT in patients with triple-negative breast cancer of different stages: objective response rate was 90.0 ± 4.7 %, grade IV treatment pathomorphosis was 50.0 ± 7.9 %.Grade IV treatment pathomorphosis for NAPCT per АС + Т scheme was achieved in 50.0 ± 7.9 % cases, for intensified regimen - in 62.5 ± 12.5 % cases. Rate of grade IV treatment pathomorphosis was higher in patients with hereditary form of the disease (62.5 ± 18.3 %) compared to the group with sporadic breast cancer (46.9 ± 8.8 %), р >0.05. In all patients, 2-year disease-free survival was 92.5 %, 2-year overall survival was 95 %.